The effect of antibiotics on the periodontal treatment of diabetic patients with periodontitis: A systematic review and meta-analysis - Tang, Ziwei; Fan, Qi; Jiang, Qingsong; Li, Xiaolong; Wang, Yan; Long, Hu; Lai, Wenli; Jian, Fan (Frontiers in Pharmacology, 2023)
Background: The aim of this meta-analysis was to compare the effects of periodontal treatment with or without adjunctive antibiotic on periodontal status and blood glucose level in diabetic patients with periodontitis. Methods: A search using electronic database (MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials) and a manual search were performed up to July 2022. Eligible 13 RCTs were included according to inclusion and exclusion criteria. Reviewers independently performed data screening, data selection, data extraction, and risk of bias. Quality assessment was performed according to the Cochrane Handbook for Systematic Reviews of Interventions. Weighted mean differences and 95% confidence intervals (CIs) for continuous outcomes were calculated using random or fixed-effects models. This review is registered in the PROSPERO database (CRD42022347803). Results: Of the 13 included articles, eight were on the use of systemic antibiotics and five on topical antibiotics. The results showed statistically significant improvement in periodontal status (probing depth, clinical attachment loss and bleeding on probing) at 6 months with systematic antibiotics use (PD-6M p = 0.04, BOP-6M p < 0.0001, CAL-6M p = 0.002). The improvement in PD with topical antibiotics was statistically significant at 1 month (p = 0.0006). However, there was no statistically significant improvement in periodontal status at 3 months with adjuvant systemic antibiotics. Conclusion: Antibiotics can improve the periodontal condition of diabetic patients with periodontitis to a certain extent. In clinical practice, it is necessary to comprehensively consider the balance of benefits and risks before deciding whether to use antibiotics. Systematic Review Registration: Identifier CRD42022347803, https://www.crd.york.ac.uk/PROSPERO/.